Withdrawal: Botham AD. Suicide: Exploring the Relationship Between Modality and Population Demographic (San Mateo County, CA, USA 2007–2018): A Population‐Based Study. J Forensic Sci 2019;64(6):1750‐60 (https://onlinelibrary.wiley.com/doi/10.1111/1556-4029.14090). Issue 3 (27th April 2020) - Unknown
Abstract : The above article, first published online on June 03, 2019, in Wiley Online Library, has been withdrawn at author's request, and in agreement between the author, the JFS Editor‐in‐Chief (Dr. Michael Peat), and John Wiley & Sons Ltd. The withdrawal has been agreed to by all parties given the article includes sensitive data which was not authorized for publication.